Simultaneous assay for protease activities of hepatitis C virus and human immunodeficiency virus based on fluorescence detection - Tsutomu Kabashima (Nature Portfolio, 2019)
Abstract Hepatitis C virus protease (HCV-PR) and human immunodeficiency virus protease (HIV-PR) are important for virus maturation, and thus can be used as potential target molecules for the development of antiviral drugs for the treatment of viral infections. In this study, a novel assay was developed to determine HCV-PR activity. This assay is based on a fluorogenic reaction, in which peptide fragments generated from an acetyl peptide substrate by HCV-PR can be selectively converted into a fluorescent derivative, and quantified by high-performance liquid chromatography (HPLC) with fluorescent detection. Herein, several acetyl-peptides can be used as substrates for HPLC. The application of this assay was further validated by simultaneous detection of HCV-PR and HIV-PR in a reaction mixture. The proposed method can differentiate the enzyme activities of HCV-PR and HIV-PR in a sample using their corresponding substrates. The results suggest that this assay can detect various proteases by employing set of substrate peptides under the same reaction conditions.